Tanaman Lotus sebagai Ide Penciptaan Karya Seni Grafis Relief Print - Wiliza, Delvi; Irwan, Irwan (Lembaga Yasin AlSys, 2025)
The creation of this relief print graphic art themed on the lotus plant employed the Consortium of Art method (Panduan Tugas Akhir Pendidikan Seni Rupa, 2021:78), which comprises five stages: preparation, elaboration, synthesis, concept realization, and completion. The preparation stage involved exploration, observation, and the collection of references related to the lotus. Elaboration included an in-depth study of the lotus’s visual form and philosophical meaning through literature, images, and videos. The synthesis stage produced a visual concept design that combined the aesthetics and symbolism of the lotus. Concept realization was carried out through the technical process of relief printing, starting from sketching, digital processing, carving, and printing to finishing. The completion stage encompassed exhibition, cataloging, and artwork evaluation. Of the ten works produced, the lotus was presented not only as a visual object but also as a symbol of strength, patience, serenity, and usefulness. Challenges encountered included limited initial ideas, scarce literature on lotus symbolism, and technical issues such as inconsistent ink mixtures and printing plate misalignment. These obstacles were addressed through academic guidance and intensive visual exploration. This creative process provided a profound understanding of the artistic process alongside technical skills in printmaking, resulting in artworks that serve not only as artistic achievements but also as a medium for conveying philosophical messages that inspire viewers to reflect on life’s values embodied by the lotus flower.